20 Years Beyond the Crossroads: The Path to Interprofessional Education at U.S. Dental Schools. Issue 8 (1st August 2015) - Palatta, Anthony; Cook, Bryan J.; Anderson, Eugene L.; Valachovic, Richard W.
Abstract : In 2003, the Institute of Medicine (IOM) called for interprofessional education (IPE) to be adopted by the health professions education community as the pedagogical approach to educating future practitioners for practice in multidisciplinary teams. In dentistry, this call built on points made in the key 1995 IOM report Dental Education at the Crossroads . Currently, IPE and collaborative practice are among the most significant changes to health care education and delivery in the 21 st century. This report describes the path that dental education has taken regarding IPE since the first national report on the subject was released in 1995. It also reports the results of a 2014 survey of U.S. dental schools to ascertain their progress in adopting and implementing IPE, as well as perceived obstacles that persist. Of the 63 dental schools, 62 participated, for a response rate of 98%. While over 90% of the respondents reported that their schools offer IPE experiences, only 58.1% had formal university‐led and ‐promoted IPE programs. Formal IPE experiences were more prevalent at public institutions (67.6%, compared with 44% of private institutions). In 2012, a previous study reported that 66% of the IPE experiences offered to dental students were voluntary; today, 69.1% of these activities are required. Interprofessional core competencies occupy four of the top five content areas of IPE programming, providing a framework for schools to implement IPE activities. However, finding the bandwidth within the dental curriculum to accommodate IPE competencies, identifying adequate time in the schedule, providing faculty training, and assessing IPE activities were the most frequently reported challenges. The results of this survey lead to recommendations for academic dental institutions moving through this transitional phase in adopting IPE.